PENGEMBANGAN DESAIN ARSITEKTUR DAN INTERIOR YANG REHABILITATIF SEBAGAI PENDUKUNG PENYEMBUHAN SECARA PSIKOLOGIS PADA RUMAH SAKIT IBU DAN ANAK - Utomo, Dian Cahyo (Universitas Aisyiyah Yogyakarta, 2018)
Abstract: Given that maternal mortality rate at delivery in Indonesia is still very high, according to UNFPA data in 2013, maternal mortality at delivery is 359 deaths per 100,000 live births. This research aims to create a guideline in the design of maternity and child hospital design that is comfortable and rehabilitative, and able to facilitate the requirement of health services especially children, both mentally and psychologically. This research includes a design guideline that can support not only medically healing patients, but can also support psychological healing. As the concept of green open space design in a room designed to minimize a child's terrifying hospital image, the creation of a child supporting IRNA can keep an intensely ill child, and the concept of maternal IRNA that can be as comfortable as possible , with the aim that pregnant mothers can remain calm at the time of therapy. Creation of supporting facilities and infrastructure for a mother who has fear in childbirth normally.Keywords: Maternal mortality rate, psychological, rehabilitative, maternal and child hospital.